2010
DOI: 10.1016/j.exer.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

αA-Crystallin associates with α6 integrin receptor complexes and regulates cellular signaling

Abstract: Abstractα-crystallins are small heat-shock proteins important to lens transparency that provide the lens with its refractive properties. In their role as molecular chaperones, these crystallins also prevent protein aggregation, affect cytoskeletal remodeling, enhance resistance to cell stress, and provide lens cells with protection against apoptosis. While many of the functions assigned to αA-crystallin are attributable to its presence in the cytoplasm of lens cells, αA-crystallin also has been detected at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(133 reference statements)
1
7
0
Order By: Relevance
“…Apoptotic cell death has been reported in developing lenses of ␣A/␣B crystallin double knock-out mice, and associated with the induction of high levels of caspase-3 (80). Interestingly, we found that ␣A-crystallin associates with ␣6 integrin receptor complexes in regions of active lens cell differentiation (81). Furthermore, activation of ␣6 integrin following exposure to PMA induced recruitment of ␣A-crystallin to ␣6 integrin receptor complexes, providing evidence of a direct signaling connection between ␣6 integrin and ␣A-crystallin (81).…”
Section: Discussionsupporting
confidence: 48%
“…Apoptotic cell death has been reported in developing lenses of ␣A/␣B crystallin double knock-out mice, and associated with the induction of high levels of caspase-3 (80). Interestingly, we found that ␣A-crystallin associates with ␣6 integrin receptor complexes in regions of active lens cell differentiation (81). Furthermore, activation of ␣6 integrin following exposure to PMA induced recruitment of ␣A-crystallin to ␣6 integrin receptor complexes, providing evidence of a direct signaling connection between ␣6 integrin and ␣A-crystallin (81).…”
Section: Discussionsupporting
confidence: 48%
“…The intracellular signalling mediators for integrin signalling, such as focal adhesion kinase (FAK) (Kokkinos et al, 2007) and ILK (Cammas et al, 2012;de Iongh et al, 2005;Weaver et al, 2007) are expressed in the lens and there are indications that these molecules have altered activity in some cataracts (Menko and Andley;Weaver et al, 2008). Moreover, recent studies using the nestin-Cre and Le-Cre lines have demonstrated a requirement of ILK for cell survival and matrix deposition during lens development (Cammas et al, 2012;Samuelsson et al, 2007).…”
Section: Ilk Modulates Extracellular Matrix and Focal Adhesionsmentioning
confidence: 99%
“…Thus, pro-regenerative effects of crystallins may, at least partially, be attributed to the regulation of the RhoA/ROCK/cofilin pathway (Wang et al, 2011 ). Because α-crystallin interacts with α6-integrin membrane receptor complexes and alters their cellular signaling (Menko and Andley, 2010 ) a speculative link to RhoA consists in the prevention of the GDP to GTP exchange of RhoA through integrin membrane complex binding of guanine nucleotide exchange factors (Wettschureck and Offermanns, 2002 ).…”
Section: Effects Of Rock Inhibitionmentioning
confidence: 99%